2011
DOI: 10.1063/1.3552599
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the forward and reverse bias I-V characteristics on Au/PVA:Zn/n-Si Schottky barrier diodes in the wide temperature range

Abstract: In this study, the forward and reverse bias current-voltage (I-V) characteristics of Au/Zinc acetate doped polyvinyl alcohol/n-Si Schottky barrier diodes (SBDs) have been investigated over the temperature range of 80-400 K. The values of zero-bias barrier height evaluated from forward and reverse bias I-V data, (ФBFo) and (ФBRo), increase with increasing temperature, and a discrepancy is observed between the values of ФBFo and ФBRo. Because the apparent barrier height (BH) seen from metal to semiconductor is h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…According to the typical diode characteristics, it can be concluded that the film formed a robust Schottky contact with the P-Silicon substrate. The curve is also in good accordance with Richardson-Dushman thermionic emission theory [10,11]. It is worth noting that the light was incident from the Si substrate side, in order to study the Bi2Se3/H-Si heterostructure.…”
Section: Resultssupporting
confidence: 81%
“…According to the typical diode characteristics, it can be concluded that the film formed a robust Schottky contact with the P-Silicon substrate. The curve is also in good accordance with Richardson-Dushman thermionic emission theory [10,11]. It is worth noting that the light was incident from the Si substrate side, in order to study the Bi2Se3/H-Si heterostructure.…”
Section: Resultssupporting
confidence: 81%
“…Ideality factor greater than unity is generally attributed to the presence of bias-dependent Schottky barrier height. The bias-dependent BH arises due to defects, interfacial layer and interface inhomogeneities [2,14]. The larger R s values in the modified diode may be due to the extra resistance offered by organic interlayer.…”
Section: Capacitance-voltage Characteristicsmentioning
confidence: 99%
“…Integrating organic molecules with semiconductors has opened wide opportunities in many areas of bioengineering, sensing, etc., which are difficult to achieve by either one alone [1]. In this context, modification of M-S contacts by organic molecules is noteworthy [2]. A thin molecular overlayer on the semiconductor can drastically modify the surface electronic properties of the semiconductor by reconstruction or creating an interfacial dipole layer [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intersecting voltage values are at nearly 1.5 V and 2.7 V for SC and DC heterostructures, respectively. The intersection behavior of the I-V curves of Schottky barrier diodes (SBDs) measured at different temperatures were discussed by some of the authors in their theoretical and experimental studies [26][27][28][29][30][31]. Among these study, Chand [26] argues that the intersection behaviors of the ln(I)-V curves are an inherent property even of homogeneous SBDs of constant barrier height and are normally hidden due to saturation in current caused by series resistance.…”
Section: The Modelmentioning
confidence: 99%